2011
DOI: 10.3946/kjme.2011.23.4.305
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Content of the Medical Knowledge Written Examination and Clinical Skill Score in Medical Students

Abstract: Based on our study, comprehensive clinical knowledge is required for medical students to gain the appropriate clinical skills. Therefore, clinical skill practice and lectures that are based on the level of comprehensive clinical knowledge are recommended in the education of clinical skills in medical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…A survey indicated that adopting the clinical skills test in the KMLE improved the quality of medical school education ( Table 1 ) [ 5 ]. A high score on the written test does not always guarantee a satisfactory score on the clinical skills test, as an analysis of examination results has shown that some examinees who received high scores on the written test failed the clinical skills test [ 7 ]. Some examinees who failed the clinical skills test in 2013 also failed the written test, with a mean score of 213 (range, 123 to 239; SD=23.5).…”
Section: Resultsmentioning
confidence: 99%
“…A survey indicated that adopting the clinical skills test in the KMLE improved the quality of medical school education ( Table 1 ) [ 5 ]. A high score on the written test does not always guarantee a satisfactory score on the clinical skills test, as an analysis of examination results has shown that some examinees who received high scores on the written test failed the clinical skills test [ 7 ]. Some examinees who failed the clinical skills test in 2013 also failed the written test, with a mean score of 213 (range, 123 to 239; SD=23.5).…”
Section: Resultsmentioning
confidence: 99%
“…Their authors combined the scores of theories, 3D spotter’s practical knowledge, and OSCE’s to examine the overall performance of students [22]. Some have shown that comprehensive clinical knowledge is required for medical students to gain the appropriate clinical skills [23].…”
Section: Discussionmentioning
confidence: 99%
“…학생들은 1, 2, 3학년 평점과 4학년 CPX 진단고사 성적 간에 유의한 상관성(0.25, 0.41, 0.59)을 보였다. 3학년 임상의학종합평가 성적이 4학년 CPX 진단고사 성적과 보인 상관성(0.29)은 기존의 연구 결과[ 12 , 13 ]에서 보였던 상관성에 비하여 약하였다. 반면 임상의학종합평가 성적은 1, 2학년 평점과는 강한 상관성(0.77, 0.80)을 보였다.…”
Section: 고찰unclassified